Dinamika Hubungan Berbatu antara Indonesia dan Organisasi Papua Merdeka (OPM) - Hilmani, Fuad; Sari, Deasy Silvya; Yulianti, Dina (Global and Policy Journal of International Relations, 2024)
The conflict between the Indonesian government and the Free Papua Movement (OPM) in Papua province has been ongoing for decades. The OPM supports Papuan independence and the conflict involves violence, armed confrontations and human rights violations. Although the Indonesian government has issued five policies to resolve this conflict, these efforts have not been very significant. The Free Papua Organization continues to wage armed resistance and attempts to secede from Indonesia. This conflict requires a collaborative and holistic approach to find a solution without further casualties.Keywords: Conflict, Papua, OPM, Indonesia, Independence, Violence, Policy, Armed Resistance, Collaborative Approach, Solution.Konflik antara Pemerintah Indonesia dan OPM (Organisasi Papua Merdeka) di provinsi Papua telah berlangsung selama beberapa dekade. OPM mendukung kemerdekaan Papua dan konflik ini melibatkan kekerasan, konfrontasi bersenjata, dan pelanggaran hak asasi manusia. Meskipun Pemerintah Indonesia telah mengeluarkan lima kebijakan untuk menyelesaikan konflik ini, upaya tersebut belum terlalu signifikan. Organisasi Papua Merdeka terus melakukan perlawanan bersenjata dan upaya pemisahan diri dari Indonesia. Konflik ini memerlukan pendekatan kolaboratif dan holistik untuk menemukan solusi tanpa memakan korban lagi. Kata kunci: Konflik, Papua, OPM, Indonesia, Kemerdekaan, Kekerasan, Kebijakan, Perlawanan Bersenjata, Pendekatan Kolaboratif, Solusi.DOI: https://doi.org/10.33005/jgp.v12i01.4219